SUPERVISI AKADEMIK DENGAN TEKNIK KLINIS UNTUK MENINGKATKAN KINERJA GURU DALAM PEMBELAJARAN TEMATIK KURIKULUM 2013 PADA SD SE-KECAMATAN GISTING - Daryono, Daryono; Kusuma, Nurhadi; muhtarom, muhtarom (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2019)
This study begins with the condition of the implementation of the 2013 Curriculum thematic learning for grade 1 and 4 teachers in SD N 1 Gisting Permai, SD N 2 Gisting Permai and SD N 1 Gisting Atas who just implemented one semester is still not optimal and found various obstacles. This study aims to improve teacher performance in the 2013 curriculum thematic learning through clinical technical academic supervision and find out the magnitude of teacher performance improvement in the 2013 curriculum thematic learning after academic supervision activities with clinical techniques in SD Gisting Subdistrict even semester 2017/2018 academic year.This research method refers to the procedure of action research (action research) carried out in three cycles for six meetings each cycle with the steps of planning, implementing actions, observing and reflecting.The results of the academic supervision actions with clinical techniques for 3 cycles on the performance of the teacher in preparing RPP the final value of RPP in the first cycle averaged 77.8; cycle II averaged 81.8 and cycle III averaged 85.7 with a cumulative increase of 7.9 and the implementation of 2013 curriculum curriculum thematic class 1 and 4 teachers the final value of the first cycle averaged 77.2, cycle II on average 85.7 and cycle III averaged 90.7 with a cumulative increase of 13.5. Thus it was concluded that the increase in teacher performance in the 2013 curriculum thematic learning after akaedical supervision with clinical technique in the elementary school of Gisting Subdistrict in the semester of 2017/2018 school year and the magnitude of teacher performance improvement in the 2013 curriculum thematic learning after academic supervision with clinical techniques at the Elementary School Even semester Gisting for the 2017/2018 school year, namely the performance of teachers in compiling thematic RPPs cycles I, II, III experienced a cumulative increase of 7.9 and teacher performance in thematic learning had a cumulative increase of 13.5.Keywords: Clinical supervision, RPP, thematic learning.